PERBEDAAN KEBOCORAN MIKRO FIBER REINFORCED COMPOSITE PREFABRICATED DAN FIBER REINFORCED COMPOSITE FABRICATED SEBAGAI PASAK SALURAN AKAR - , DIDI MURTIADI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fiber reinforced composite (FRC) is often used as restorative material after root canal treatment mostly because of its esthetic and mod of elasticity that can be expected retention with crown restoration after endodontic treatment. Polymerization shrinkage of resin cement would cause interfacial gap between FRC post and root canal dentin wall. The aim of this study was to evaluate the microleakage of prefabricated FRC and fabricated FRC used as root canal post. In this study 20 mandibular premolar were used as research subjects where the crown were removed to obtain uniform root length of 18 mm. The root canal was prepared using crown down technique, obturated with guttapercha using single cone technique, which then kept in an incubator for 72 hours at 37â°C. The subjects were randomly divided into 2 groups of 10, group I was restored with prefabricated FRC post and group II with fabricated FRC post. After the subjects were coated with nail polish followed by sticky wax, the subject were immersed in 2% methylene blue solution for 1 week. After rinsing and cleaning of the subject, they were cut mesio-distally. The penetration of the dye was measured using stereo microscope of 60x magnification. The result was analyzed using t test. The results showed that there was a significant differences on the microleakage of prefabricated FRC post and fabricated FRC post (p<0.05), where the microleakage of prefabricated fRC post was higher than fabricated FRC post (p =0.003).